Metodologia de revisão e atualização de tesauros aplicada ao Tesauro de Contas de Minas Gerais: abordagem da pesquisa-ação - Ana Carolina Ferreira (2020)
Introduction: Thesauri are terminological instruments that mediate information communication in information retrieval systems, characterized by the dynamics of their terminology. Motivation/problem: This investigation was motivated by the professional management practice of the Minas Gerais Accounts Thesaurus and the inexistence, in the literature, of a systematized and unified methodology for the review and updating of Thesauri. Assumptions: The guiding assumptions were based on the concepts that the standards ISO 25.964-1 (2011) and ANSI/NISO Z39.19-2005 (R2010), the Faceted Classification Theories (FCT), of Concept, of Terminology and of Linguistics support the review and updating process of Thesauri, and that the research-action approach is aligned with this activity, allowing the modelizer to immerse in the modeled reality. General objective: In this scenario, the research objective was to “propose a review and updating methodology of Thesauri, applied to the Minas Gerais Accounts Thesaurus, based on the research-action approach, for greater semantic consistency within information representation in the domain of external control.” Referential: The theoretical framework includes the theoretical-conceptual contributions of the FCT, especially the fundamental categories, canons and analytical-synthetic principles for the organization of the conceptual system, and the Concept Theory, particularly regarding the criteria for elaborating definitions and delimiting the characteristics of the concepts. The Terminology principles were also covered, especially those referring to language for specific purposes (LSP), which comprise the meaning of the term in the context and extraction of semantic traits of definitions in order to determine the characteristics of the concepts. Linguistic, logical and semantic elements were also fundamental for establishing semantic relationships. Setting: The description of the research environment brought inputs to understand the external control, focusing on the performance of the audit courts, and the public accounting framework, under the patrimonial approach. Methodology: The methodology was based on the philosophical pragmatic concept, characterized as a qualitative approach, exploratory objective, applied nature and adoption of the action-research method. The research universe consists of the totality of the conceptual structure of the Minas Gerais Accounts Thesaurus, with a Patrimonial Accounting thematic basis. The research development was based on five macro-stages: 1) identification of the problem situation; 2) exploratory stage; 3) in-depth study stage; 4) intervention stage, and 5) research results of evaluation and dissemination stage. Results: The results indicated that semantic relationships are the modeling principle, which should be established based on theoretical and normative criteria, consistent definitions and domain knowledge. The definitions were fundamental for understanding the semantics and identity of the concepts and the basis for all conceptual modeling. The results revealed that the action-research approach allowed the integration and participation of the different actors in the process, combining academic knowledge with professional practice. Conclusions: The conclusions show that the proposed methodology has a general capacity for conceptual modeling in other contexts and instruments. Regarding the external control scope, the contribution is observed in the standardization of terminology, supporting its use in information retrieval systems focused on audits based on electronic information, according to the most modern auditing concept. In relation to the interests of Librarianship and Information Science, we perceive the need for studies and research on Thesauri, with the study of definitions as inspiration.